Role Of Enos (Glu298asp) Gene Polymorphism And Intergenotypic Variation Of Nitric Oxide & Inflammatory Cytokines In Preeclampsia. - DEEPIKA SHARMA; SHUBHA. S. TRIVEDI; JAYASHREE BHATTACHARJEE (International Journal of Pharma and Bio Sciences, 2010)
Multiple etiologies are available for understanding the mechanisms responsible for the syndrome of Preeclampsia. Cytokine imbalance and endothelial dysfunction is suggested to have a pivotal role. The pathophysiological processes in preeclampsia (PE) are also influenced by genetic factors. To characterize the host genetic factors determining the susceptibility to Preeclampsia, we evaluated the influence of polymorphism in eNOS gene on nitric oxide and cytokines production and on the risk of developing PE. This cross-sectional study included 150 women with preeclampsia and 150 healthy pregnant women. Their blood samples were analyzed for nitric oxide, inflammatory cytokines and eNOS gene polymorphism. Decreased NO (reflecting endothelial dysfunction) and increased cytokines (interleukin-6, Tumor Necrosis Factor-a, interleukin-2 and Interferon-g) levels were found in preeclampsia (p<0.001). Significant differences were found in genotype/allele distribution between two groups. Significant negative correlation was seen between NO and cytokines levels (IL-6, TNFa, INFg & IL-2) in preeclamptic group (p=0.001). We concluded that endothelial dysfunction and inflammatory markers could be involved in the pathogenesis of Preeclampsia and those markers could be correlated with genotypic variations.